Genome-wide meta-analysis identifies novel loci of plaque burden in carotid artery. (April 2017) - Pott, Janne; Burkhardt, Ralph; Beutner, Frank; Horn, Katrin; Teren, Andrej; Kirsten, Holger; Holdt, Lesca M.; Schuler, Gerhard; Teupser, Daniel; Loeffler, Markus; Thiery, Joachim; Scholz, Markus
Abstract: Background and aims: Carotid artery plaque is an established marker of subclinical atherosclerosis and common patho-mechanisms with coronary artery disease (CAD) are hypothesized. We aimed to identify genetic variants associated with carotid plaque and to examine the potential shared genetic basis with CAD. Methods: After investigating the reliability of plaque detection, we performed a genome-wide meta-association study in two independent cohorts (LIFE-Adult, n = 4037 and LIFE-Heart, n = 3152) for carotid plaque score (PS), defined as the sum of the plaque load of common carotid artery and carotid bulb. Further, we analyzed whether previously reported CAD and stroke loci were also associated with PS. Results: We identified two loci with genome-wide significance for PS. One locus is the known CAD-locus at chromosome 9p21 (lead SNP rs9644862, p = 8.73 × 10 −12 ). We also describe a novel locus on chromosome 10q24 within the SFXN2 gene as the most probable candidate (lead SNP rs2902548, p = 1.97 × 10 −8 ). In addition, 17 out of 58 known CAD loci and six of 17 known stroke loci were associated with PS at a nominal level of significance. Conclusions: We showed that PS is a reliable trait to analyze genetics of atherosclerosis. Two new loci of genome-wide significant association with PS were found. The observed non-random overlap of CAD and PS associations strengthens the hypothesis of a shared genetic basis for these atherosclerotic manifestations. Highlights: We performed genome-wide association analysis of carotid plaque (PS) in two cohorts. We detected two loci with genome-wide significance and two with suggestive evidence. 9p21 locus of coronary artery disease (CAD) showed strongest association with PS. We observed an enrichment of PS associations for known CAD loci.